2015
DOI: 10.1016/j.patcog.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

META-DES: A dynamic ensemble selection framework using meta-learning

Abstract: Dynamic ensemble selection systems work by estimating the level of competence of each classifier from a pool of classifiers. Only the most competent ones are selected to classify a given test sample. This is achieved by defining a criterion to measure the level of competence of a base classifier, such as, its accuracy in local regions of the feature space around the query instance. However, using only one criterion about the behavior of a base classifier is not sufficient to accurately estimate its level of co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
140
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(142 citation statements)
references
References 38 publications
0
140
0
2
Order By: Relevance
“…Finally, a series of methods have been developed recently under the common name 'dynamic model selection' [10], [16], [17], [17]- [21]. These approaches take an ensemble of base classifiers (e.g, from bagging), then attempt to learn a high-level classification model using, for example, instanceinstance similarities and model-model correlations, as input features.…”
Section: Ice Differs From Most Existing Ensemble Methods Significantlmentioning
confidence: 99%
“…Finally, a series of methods have been developed recently under the common name 'dynamic model selection' [10], [16], [17], [17]- [21]. These approaches take an ensemble of base classifiers (e.g, from bagging), then attempt to learn a high-level classification model using, for example, instanceinstance similarities and model-model correlations, as input features.…”
Section: Ice Differs From Most Existing Ensemble Methods Significantlmentioning
confidence: 99%
“…A total of 15 sets of meta-features are considered, with ten sets proposed in this paper, and five coming from our previous work [6]. Each set f i captures a different property of the behavior of the base classifier, and can be seen as a different criterion to dynamically estimate the level of competence of the base classifier, such as the classification performance estimated in a local region of the feature space and the classifier confidence for the classification of the input sample.…”
Section: Meta-feature Extractionmentioning
confidence: 99%
“…Then, only the classifier(s) that attain a certain competence level, are used to predict the label of the given test sample. Recent works in the MCS literature have shown that dynamic ensemble selection (DES) techniques achieve higher classification accuracy when compared to static ones [5,6,7]. This is especially true for ill-defined problems, i.e., for problems where the size of the training data is small, and there are not enough data available to train the classifiers [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some works of dynamic classifier selection (DCS) [7], [8] use other measures, beyond accuracy, to calculate the competence. Recent works on DCS [9], [10], [11] use the composition of many measures to determine the competence of the classifiers, selecting and combining them to predict the class of the test pattern.…”
Section: Introductionmentioning
confidence: 99%